Differences between SNAGS and Mc Kenzie Interventions with Core Stability and Mc Kenzie on the Functional Ability of Elderly People with Lumbar HNP Conditions at Hermina Hospital Depok - Megawanty, Irma; Maulina, Luluk (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: HNP is a degenerative disease where the elasticity of the annulus fibrosus decreases so that it becomes one of the causes of LBP and often occurs in the elderly. One of the roles of physiotherapy in HNP cases can be treated with exercise therapy, with the SNAGS and Mc Kenzie intervention methods as well as with Core Stability and Mc Kenzie. To help improve the functional abilities of the elderly. The purpose of the study is to determine the differences in interventions for Lumbar HNP cases using the SNAGS and Mc Kenzie methods as well as Core Stability and Mc Kenzie on the functional abilities of the elderly. Methods: The design of this study used a quasi-experimental with two groups pre-post test. A sample of 22 people was selected by purposive sampling which was divided into two, namely treatment 1 and treatment 2. The research was conducted for 4 weeks consisting of one pretest, with meetings twice a week with a duration of 30-45 minutes and one post-test. The instrument used is the ODI questionnaire. Results: The result showed that the normality test using the Shapiro-Wilk test resulted in a value of p=0.000, which means it was significant in both treatment groups. From the results of the paired test, it is significant with a value of p = 0.000 meaning p <0.05. The reduction of the difference in the percentage of disability in treatment group 1 was -32.55 per cent, and in treatment group 2 was -37.27 per cent. Conclusion: The conclusion from the study is SNAGS and Mc Kenzie interventions as well as Core Stability and Mc Kenzie can affect the functional abilities of the elderly. With more effective results on Core stability and Mc Kenzie interventions in improving the functional abilities of the elderly with Lumbar HNP conditions.